Suggestion of an analysis of three novels by Amin Maalouf : Léon l'Africain, Samarcande, Les Jardins de lumière - (:unkn) unknown (My University, 1998)
The first three novels of Amin Maalouf, the lebanese writer, writing in French (Leon the African, 1986, Samarcande, 1988 and The Gardens of Light, 1991), offer an example of the kind of questions raised by the practice of the historical novel in the current period. Anxious to offer to readers the precise images of a reconstituted past, not only of its most concrete daily reality, but especially of its mentalities and its ideology ; the three novels strive to derive the elements of a reflection which is inscribed in the actual context of the arab world. Maalouf neutralizes each form of relationship between flight or homesickness with respect to this past. Putting in relation, directly or indirectly, the past and the present, he invites the reader to be conscious of the problems created in the history by the disparities of races, of religion, and of civilization. Maalouf's novel claims for a right of inspection on the arab world crisis, and also of the issues that can permit to resolve it.
Keywords: African Research